Morpho-Physiological and Proteomic Response of Bt-Cotton and Non-Bt Cotton to Drought Stress - Nagamalla, Swetha Sudha; Alaparthi, Malini Devi; Mellacheruvu, Sunitha; Gundeti, Ravindar; Earrawandla, Jana Priya Sony; Sagurthi, Someswar Rao (Frontiers in Plant Science, 2021)
Drought stress impacts cotton plant growth and productivity across the countries. Plants can initiate morphological, cellular, proteomic changes to adapt to unfavorable conditions. However, our knowledge of how cotton plants respond to drought stress at the proteome level is limited. Herein, we elucidated the molecular coordination underlining the drought tolerance of two inbred cotton varieties, Bacillus thuringiensis-cotton (Bt-cotton + Cry1 Ac gene and Cry 2 Ab gene; NCS BG II BT (BTCS/BTDS)) and Hybrid cotton variety (Non-Bt-cotton; (HCS/HDS)). Our morphological observations and biochemical experiments showed a different tolerance level between two inbred lines to drought stress. Our proteomic analysis using 2D-DIGE revealed that the changes among them were not obviously in respected their controls apart from under drought stress illustrate differential expression of 509 and 337 proteins in BTDS and HDS compared to their controls. Among these, we identified eight sets of differentially abundant proteins (DAP) and characterized using MALDI-TOF/TOF mass spectrometry. Further, the quantitative real-time qRT-PCR analysis was carried out with the identified drought-related proteins and confirmed differential expressions. Insilico analysis of differentially expressed proteins using Cytoscape network finds ATPB, NAT9, ERD, LEA, and EMB2001 to various drought-responsive genes LEA, AP2/ERF, WRKY, NAC, and functionally correlative. These proteins play a vital role in transcriptomic regulation in response to drought stress. The higher drought response in Bt cotton (BTCS/BTDS) attributed to the overexpression of photosynthetic proteins, enhanced lipid metabolism, increased cellular-detoxification, activation chaperones, and reduced synthesis of unwanted proteins. Thus, Bt variety had enhanced photosynthesis, elevated water retention potential, balanced leaf stomata ultra structure, substantially increased antioxidant activity than the Non-Bt cotton. Our results may aid breeders and provide further insights into developing new drought-tolerant and high-yielding cotton hybrid varieties.